Theological Issues of Pandemic Covid 19 in Malaysia: The Views of The Muslims Theologians - Roslizawati Mohd Ramly (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2022)
The outbreak of the pandemic COVID-19 in Malaysia started in March 2020. has not only affected Muslims well-being in terms of socio-economic, emotional, and mental health, but it has also challenged their theological understandings, specifically relating to the issue of Qada' and Qadar and Human Freedom of Will. Consequently, some Muslims refused to observe the government order to contain the spread of COVID-19 and accused the observant of the order of committing polytheism. To clarify the issue, this study aims to identify the theological perspectives of the Muslim theologians on COVID-19 and the methods to prevent it. This study employed a qualitative descriptive method. Data was collected through Youtube videos that contain views and responses of the well-known Muslim theologians from the school of Ahl Sunnah wal Jamaah on the theological issues related to the pandemic. The study found that the view of the Muslim theologians on COVID-19 shows that they uphold the Asha'rites understanding and teachings of the concept of Qada' and Qadar and human freedom of will. Therefore, they regarded the observant of the SOP or Islamic guidelines in preventing the spread of pandemic Covid 19 as a form of ikhtiyar and not as a form of polytheism.